Mobile contingency management as an adjunctive treatment for co-morbid cannabis use disorder and cigarette smoking. (April 2018) - Beckham, Jean C.; Adkisson, Kelsie A.; Hertzberg, Jeffrey; Kimbrel, Nathan A.; Budney, Alan J.; Stephens, Robert S.; Moore, Scott D.; Calhoun, Patrick S.
Abstract: Introduction: Cannabis is the most widely used illicit drug in the U.S. with 19.8 million current users. Population-based data indicate that almost all cannabis users (90%) have a lifetime history of tobacco smoking and the majority (74%) currently smoke tobacco. Among cannabis users, smoking tobacco is associated with increased frequency of cannabis use, increased morbidity, and poorer cannabis cessation outcomes. There is a lack of research, however, focused on addressing cessation of both substances simultaneously. The purpose of the current pilot study was to evaluate the feasibility and acceptability of a multi-component tobacco/cannabis abstinence treatment. Methods: Five participants completed Abstinence Reinforcement Therapy, an intervention that included five sessions of cognitive-behavioral telephone counseling for tobacco/cannabis, pharmacotherapy for smoking cessation, and five weeks of mobile contingency management to remain abstinent from tobacco and cannabis. Results: Feasibility of recruitment, retention and treatment completion was high. Satisfaction with the treatment was also high. Conclusion: Results support the feasibility and acceptability of this approach with dual cannabis and tobacco users and suggest that further research examining the efficacy of this approach is warranted. Highlights: Little is known about treating cessation for cannabis and tobacco use simultaneously. Participants completed Abstinence Reinforcement Therapy (ART) for both substances. ART for both cannabis and tobacco and home monitoring with saliva strips is feasible. Future research should examine the efficacy and cost-effectiveness of this approach.